Multidisciplinary interventions in a specialist Drug Development Unit to improve family history documentation and onward referral of patients with advanced cancer to cancer genetics services. (June 2019) - Moss, Cathryn A.; Cojocaru, Elena; Hanwell, Janet; Ward, Simon; Xu, Wen; van Zyl, Mary; O'Leary, Lorraine; de Bono, Johann S.; Banerji, Udai; Kaye, Stan B.; Minchom, Anna; George, Angela J.; et al.
Abstract: Background: Molecular aberrations in cancer may represent therapeutic targets, and, if arising from the germline, may impact further cancer risk management in patients and their blood relatives. Annually, 600–700 patients are referred for consideration of experimental drug trials in the Drug Development Unit (DDU) in our institution. A proportion of patients may merit germline genetic testing because of suspicious personal/family history or findings of tumour-based testing. We aimed to assess the impact of different multidisciplinary interventions on family history taking and referral rates from DDU to Cancer Genetics Unit (CGU). Methods: Over 42 months, three interventions were undertaken at different intervals: (1) embedding a genetics provider in the DDU review clinic, (2) 'traffic light' system flagging cancers with a heritable component and (3) virtual multidisciplinary meeting (MDM). Comparative analyses between intervals were undertaken, including referral rates to CGU, investigations and patient outcomes. Family history taking in a sample of 20 patients managed in each interval was assessed by a retrospective chart review. Results: Frequency of family history taking and referral to CGU, increased with each intervention, particularly, the virtual MDM (40% vs 85%). Referral rates increased over the study period, from 0.1 referral/week (5/year, 0.36% total referrals) to 1.2/week (projected 63/year, 3.81%). Forty-four (52%) patients referred required germline testing; in three of whom, variants were identified. Non-attendance rates were low (6, 7%). Conclusion: Patients in the DDU are unique, with long cancer histories and often short estimated life expectancy. Multidisciplinary working between CGU and DDU facilitates germline testing of those patients who may otherwise miss the opportunity. Highlights: Criteria for germ line genetic testing change over time. Patients with advanced cancer may miss the opportunity for genetic testing. We propose three interventions to improve rates of referral for genetic counselling. The study cohort includes patients with advanced metastatic cancer. Referral rates and family history documentation improved with each intervention.